Penggunaan Game Visual Novel Dalam Pembelajaran Menyimak Bahasa Jepang Tingkat Dasar: The Use of Visual Novel Games in Basic Japanese Listening Learning - Marhamah, Ghina Isnaeny; Sutjiati, Neneng; Dewanty, Via Luviana; Kusrini, Dewi (Jurnal Pendidikan Bahasa Jepang Undiksha, 2025)
Listening comprehension is one of the skills learned in Japanese language. Learners encounter challenges in Japanese listening comprehension, such as difficulties in understanding spoken language and in grasping narrative contexts. This study aims to investigate the effectiveness of using visual novel game as a learning media for learners in basic Japanese listening comprehension. The experimental method in this research is used to examine the utilization of visual novel game as a learning media. The use of this media obtained positive feedback from learners, as interesting illustrations help learners understand narrative contexts, while visuals and audio enhance learners’ focus and reduce weariness. There was an evident improvement in learners' listening comprehension skills, as reflected in the increase of average scores in the posttest compared to the pretest. The findings of this study are expected to provide insights for optimizing Japanese listening comprehension learning through the utilization of visual novel game media.